Cryptococcus neoformans: Tripping on Acid in the Phagolysosome - DeLeon-Rodriguez, Carlos M.; Casadevall, Arturo (Frontiers in Microbiology, 2016)
Cryptococcus neoformans (Cn) is a basidiomycetous pathogenic yeast that is a frequent cause of meningoencephalitis in immunocompromised individuals. Cn is a facultative intracellular pathogen in mammals, insects and amoeba. Cn infection occurs after inhalation of spores or desiccated cells from the environment. After inhalation Cn localizes to the lungs where it can be phagocytosed by alveolar macrophages. Cn is surrounded by a polysaccharide capsule that helps the fungus survive in vivo by interfering with phagocytosis, quenching free radical bursts and shedding polysaccharides that negatively modulates the immune system. After phagocytosis, Cn resides within the phagosome that matures to become a phagolysosome, a process that results in the acidification of the phagolysosomal lumen. Cn replicates at a higher rate inside macrophages than in the extracellular environment, possibly as a result that the phagosomal pH is near that optimal for growth. Cn increases the phagolysosomal pH and modulates the dynamics of Rab GTPases interaction with the phagolysosome. Chemical manipulation of the phagolysosomal pH with drugs can result in direct and indirect killing of Cn and reduced non-lytic exocytosis. Phagolysosomal membrane damage after Cn infection occurs both in vivo and in vitro, and is required for Cn growth and survival. Macrophage treatment with IFN-γ reduces the phagolysosomal damage and increases intracellular killing of Cn. Studies on mice and humans show that treatment with IFN-γ can improve host control of the disease. However the mechanism by which Cn mediates phagolysosomal membrane damage remains unknown but likely candidates are phospholipases and mechanical damage from an enlarging capsule. Here we review Cn intracellular interaction with a particular emphasis on phagosomal interactions and develop the notion that the extent of damage of the phagosomal membrane is a key determinant of the outcome of the Cn-macrophage interaction.